2006
DOI: 10.1002/fam.936
|View full text |Cite
|
Sign up to set email alerts
|

Measuring chemical heat production rates of biofuels by isothermal calorimetry for hazardous evaluation modelling

Abstract: SUMMARYBiofuels are commonly stored in large stacks that may heat up and self-ignite from microbiological and chemical heat production. This paper shows how isothermal (heat conduction) calorimetry can be used to measure heat production rates of biofuels at relatively low temperatures close to where self-heating starts to become a problem. Measurements can be made to assess how the reaction rate is a function of such factors as temperature, extent of reaction, oxygen pressure, water content and the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 22 publications
1
51
0
Order By: Relevance
“…For comparison Chen et al [4] found E = 90 ± 3 kJ/mol and QA = 3.19 × 10 11 W/kg for untreated sawdust. In another recent paper on wood pellets [25] it was found, by performing micro-calorimeter tests, that the apparent activation E varied from 60 to 80 kJ/mol. A comparison of the two methods' predictions of CAT at a given storage size is shown in Figures 11 and 12 for HP100 and for the 6 mm wood pellets.…”
Section: Crossing Point Resultsmentioning
confidence: 96%
“…For comparison Chen et al [4] found E = 90 ± 3 kJ/mol and QA = 3.19 × 10 11 W/kg for untreated sawdust. In another recent paper on wood pellets [25] it was found, by performing micro-calorimeter tests, that the apparent activation E varied from 60 to 80 kJ/mol. A comparison of the two methods' predictions of CAT at a given storage size is shown in Figures 11 and 12 for HP100 and for the 6 mm wood pellets.…”
Section: Crossing Point Resultsmentioning
confidence: 96%
“…As a simple model, Eq. (2) was therefore used to express the heat release rate of low temperature oxidation of coal and biomass materials in calorimeters [21,23,24,26]. Such an approach [21] was followed here to do the kinetic analysis.…”
Section: Tga-dsc Test and Kinetic Analysismentioning
confidence: 99%
“…Because the heat evolution is one of the vital properties related to the self-heating, various thermal analysis methods have been developed to directly measure the heat effect and to derive the kinetics of the low temperature oxidation [18]. Among them differential scanning calorimetry (DSC) [19][20][21][22] and isothermal calorimetry [23][24][25][26] are widely employed. While DSC is applicable for the measurements at higher temperatures prior to ignition, isothermal calorimetry allows the measurements at much lower temperatures close to where the self-heating takes place.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidation processes require oxygen in order to continue. It has been shown that the oxidative degradation process is faster and therefore gives a greater heat in wood materials, which contain higher levels of lignin [2] and that the presence of metals increased oxidation [3]. The main factors affecting the temperature of a stack with a certain type of wood fuel are: the moisture content of the material, moisture gradient in the stack when piled up, stack size, and density of the material.…”
Section: Fire Risks Related To Waste Storagementioning
confidence: 99%